Psychometric properties of the Italian version of the staff attitude to coercion scale: an exploratory factor analysis - Venturini, Paola; Bassi, Giulia; Salcuni, Silvia; Kotzalidis, Georgios D.; Telesforo, Carla Ludovica; Salustri, Eleonora; Trevisi, Manuela; Roselli, Valentina; Tarsitani, Lorenzo; Infante, Vittorio; Niolu, Cinzia; Polselli, Gianmarco; et al. (Frontiers in Psychiatry, 2023)
Aims The current study aimed to validate the Italian version of the Staff Attitude to Coercion Scale (SACS), which assesses mental health care staff’s attitudes to the use of coercion in treatment. Methods The original English version of the SACS was translated into Italian, according to the back-translation procedure. Subsequently, it was empirically validated by performing an exploratory factor analysis on a sample of 217 mental health professionals (Mean = 43.40 years, SD = 11.06) recruited form Italian general hospital (acute) psychiatric wards (GHPWs), with at least 1 year of work experience (i.e., inclusion criteria). Results Results confirmed the three-factor solution of the original version for the Italian version of the SACS, though three items loaded on different factors, compared to the original. The three extracted factors, explained 41% of total variance, and were labeled similarly to the original scale and according to their respective item content, i.e., Factor 1 “Coercion as offending” (items: 3, 13, 14, and 15), Factor 2 “Coercion as care and security” (items: 1, 2, 4, 5, 7, 8, and 9), and Factor 3 “Coercion as treatment” (items: 6, 10, 11, and 12). The internal consistency of the three-factor model of the Italian version of the SACS was assessed through Cronbach’s α and yielded acceptable indexes, ranging from 0.64 to 0.77. Conclusion The present findings suggest that the Italian version of the SACS is a valid and reliable tool that can be used to assess healthcare professionals’ attitudes toward coercion.